(untitled) (Revista de Psicología, 2024)
The aim of the present study was to analyze the effect of socioeconomic status (SES) on executive functions (EF) and metacognition in adolescents and to examine the relationship between executive performance and metacognition based on SES. The sample of 100 adolescents aged 14 to 15 years was divided into two groups: 50 adolescents from the middle socioeconomic status (Middle-SES) and 50 from the low socioeconomic status (Low-SES). The WISC-IV Working Memory (WM) Index, the Trail Making Test, and the Stroop Color and Word Test were used to assess EF. Additionally, the Metacognitive Awareness Inventory (MAI) and the Graffar-Méndez Castellano scale were used. Multivariate analysis of variance (MANOVA), multiple regressions, and Pearson’s correlation were employed. The findings revealed that the Middle-SES group outperformed the Low-SES group in tasks assessing EF, while the Low-SES group scored higher in some metacognitive skills. The mother’s educational level and profession were the main predictors of executive performance. Additionally, metacognitive skills were selectively associated with EF, with differences depending on SES. This study has significant implications for designing interventions to enhance EF and foster the development of robust metacognitive skills.